Closing the books or keeping them open? Identity work in partner retirement from Big 4 accounting firms - Azambuja, Ricardo; Baudot, Lisa; Endo, Takahiro; Matsubara, Saori (Contemporary Accounting Research, 2025)
Abstract One view of the socialization experienced by professionals in global Big 4 firms suggests that the intensity of socialization engenders a strong and deep‐rooted professional identity. We scrutinize this claim by drawing on interviews with partners who retired from lifelong employment in Big 4 firms in Japan. Through partners' reflections on their experiences in detaching from the firm, we examine how socialization manifests in partners' identity work. We find that partners' identity, which often appears entrenched, invariable, and heroic, can be highly fragile and vulnerable to changing circumstances. Before leaving the firm, interviewees attempt to reconcile their Big 4 “graduation” with feelings of obsolescence and a growing distance from previous accomplishments. After leaving the firm, interviewees revisit the identity built throughout their careers. Unable to move on to a selfhood detached from that identity, they refashion their identity relative to their former Big 4 partner self, backgrounding their private life and post‐firm professional affiliations. Not knowing how to “close the books,” retired partners seek comfort in the old “plot” and in the old “characters,” finding ways to “keep the books open” even after the “setting” has changed. Our results reconfirm the powerful socialization experienced by partners during their tenure with the Big 4 but run counter to scholarship that characterizes the identity of Big 4 partners as strong and fixed. Rather, we demonstrate the insecurity underlying our professional service heroes' identity work and the contingent identity work processes that partners engage in while navigating departure from the Big 4.